Penyelesaian Wanprestasi Dalam Perjanjian Hutang Piutang Dengan Jaminan Sertifikat Hak Milik Bersama : Analisis Putusan Nomor 66/Pdt.G/2020/PN. Sel. - Novia Apriyanti Ardani, Ni Putu; Hikmatiar Al Qindy, Fatria (Fakultas Hukum Universitas Mataram, 2024)
This research aims to explain the legal position of joint ownership certificates as collateral for debt and receivable agreements based on the judge's considerations. This research is normative legal research using statutory, conceptual, and case approaches. The land rights in this certificate include collateral for which the agreement is accessoir. Inherited property as joint ownership requires heirs to take legal action over joint property. In Decision Number 66/Pdt.G/2020/PN.Sel, regarding the plaintiff's claim regarding the collateral object, this was rejected. In Civil Procedure Law, the plaintiff should apply for collateral confiscation. Based on Article 8 Paragraph (1) UUHT, the parties providing guarantees in APHT are all heirs. So, this guarantee agreement is not legally valid.